Diamond with nitrogen: states, control, and applications. Issue 1 (2nd January 2021) - Zheng, Yuting; Li, Chengming; Liu, Jinlong; Wei, Junjun; Ye, Haitao
Abstract: The burgeoning multi-field applications of diamond concurrently bring up a foremost consideration associated with nitrogen. Ubiquitous nitrogen in both natural and artificial diamond in most cases as disruptive impurity is undesirable for diamond material properties, eg deterioration in electrical performance. However, the feat of this most common element-nitrogen, can change diamond growth evolution, endow diamond fancy colors and even give quantum technology a solid boost. This perspective reviews the understanding and progress of nitrogen in diamond including natural occurring gemstones and their synthetic counterparts formed by high temperature high pressure (HPHT) and chemical vapor deposition (CVD) methods. The review paper covers a variety of topics ranging from the basis of physical state of nitrogen and its related defects as well as the resulting effects in diamond (including nitrogen termination on diamond surface), to precise control of nitrogen incorporation associated with selective post-treatments and finally to the practical utilization. Among the multitudinous potential nitrogen related centers, the nitrogen-vacancy (NV) defects in diamond have attracted particular interest and are still ceaselessly drawing extensive attentions for quantum frontiers advance.